2018
DOI: 10.5897/ajar2017.12473
|View full text |Cite
|
Sign up to set email alerts
|

Production performance evaluation of Koekoek chickens at Adami Tulu research center

Abstract: A study was conducted to evaluate the production performance of koekoek chickens at Adami Tulu Research Center. Feed consumption, age at point of laying, annual egg production, mortality, and egg quality parameters were used as evaluation parameters. Mean feed consumption of starter, grower and layer of koekoek chickens at Adami Tulu Research Center was 56.4±4.6, 84.3±6.3 and 124±8.6 g/day, respectively. Koekoek chickens attain sexual maturity at 5 months and produce 213± 12.4 eggs per year. Their hatchability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Substantial variations have existed among exotic chicken breeds imported into the country since the 1950s and evaluated under intensive and village production systems. Recent studies that evaluated one or more of those breeds (e.g., Lemlem and Tesfay, 2010 ; Geleta et al, 2013 ; Tadesse et al, 2013 ; Geleta and Abdulkadir, 2018 ; Senbeta and Balcha, 2020 ) revealed variation in performance among Fayoumi, Koekoek, and White Leghorn breeds. For instance, those breeds annually lay 144 − 159, 187 − 213, and 173, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial variations have existed among exotic chicken breeds imported into the country since the 1950s and evaluated under intensive and village production systems. Recent studies that evaluated one or more of those breeds (e.g., Lemlem and Tesfay, 2010 ; Geleta et al, 2013 ; Tadesse et al, 2013 ; Geleta and Abdulkadir, 2018 ; Senbeta and Balcha, 2020 ) revealed variation in performance among Fayoumi, Koekoek, and White Leghorn breeds. For instance, those breeds annually lay 144 − 159, 187 − 213, and 173, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial variations have existed among the exotic chicken breeds that have been imported into the country since the 1950s and evaluated under intensive and village production systems. Recent studies that evaluated one or more of those breeds (e.g., Lemlem and Tesfay 2010 ; Geleta et al 2013 ; Tadesse et al 2013 ; Geleta and Abdulkadir 2018 ; Senbeta and Balcha 2020 ) demonstrated variations in performance among Fayoumi, Koekoek, and White Leghorn. For instance, the breeds laid 144 − 159, 187 − 213, and 173 eggs per year, respectively.…”
Section: Introductionmentioning
confidence: 99%